Elements of Success in Chicago Botanic Garden’s Science Career Continuum - Katherine A. Johnson (American Society for Microbiology, 2016)
The Science Career Continuum at the Chicago Botanic Garden is a model program for successfully encouraging youth from diverse backgrounds into STEM careers. This program has shown that when students are given an opportunity to participate in real scientific research under the mentorship of a caring professional over multiple years, they are more likely to go to college and pursue STEM careers than their peers. Journal of Microbiology & Biology Education